(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
Countries in the world in general and Vietnam in particular are entering the industrial revolution 4.0. This new revolution is profoundly affecting many different areas of social life. It gives countries the opportunity to change the socio-economic face, but potential risks and incalculable challenges. The paper focuses on analyzing the experiences of countries: Germany, the United States, Japan, Australia, China, and Korea on the opportunities and challenges posed to the impact of the industrial revolution. 4.0 and suggestions for Vietnam in response to the industrial revolution 4.0.